Targeting macrophage phenotypes to prevent diseases caused by Leishmania and Trypanosoma cruzi infections - Vellozo, Natália S.; Matos-Silva, Thayane C.; Lopes, Marcela F. (Frontiers in Immunology, 2025)
Macrophage plasticity is remarkable, and recent studies have opened new prophylactic and therapeutic avenues for immunomodulation of macrophage phenotypes in inflammatory and infectious diseases. During infections caused by the pathogenic protozoans Leishmania spp. and Trypanosoma cruzi, susceptibility to disseminated or chronic infections and/or the development of inflammatory diseases depend on the balance between protective immunity mediated by macrophages and anti-inflammatory responses. Here, we will discuss strategies that exploit macrophage plasticity towards the extreme proinflammatory M1 or pro-infection M2 phenotypes to prevent the establishment of disseminated and chronic infection or to temper parasite-driven inflammatory responses. Immunomodulation of macrophage phenotypes has been tested in experimental models of protozoan infections through pharmacological approaches, synergy between pro-M1 cytokines, and targeting of pro-M2 macrophage functions, such as efferocytosis. We will address the cellular and molecular mechanisms underlying strategies designed to redirect macrophage activation towards M1 and M2 phenotypes, as well as the challenges and open questions.